NANDA nursing diagnoses associated with the occurrence of psychomotor agitation in patients with severe mental disorder: a cross-sectional study - María-Elena G; Raúl Juárez-Vela; Pedro-Manuel Rod; Jesús Pérez; Juan-Luis S; Esther Rubinat-Arnaldo; Noelia Navas-Echazarreta; Teresa Sufrate-Sorzano; Iván Santolalla-Arnedo (BMC, 2023)
Abstract Background Psychomotor agitation is increased psychomotor activity, restlessness and irritability. People with psychomotor agitation respond by overreacting to intrinsic and extrinsic stimuli, experiencing stress and/or cognitive impairment. the aim was to analyse the association of nursing diagnoses with the disinhibition dimension, the aggressiveness dimension and the lability dimension of the Corrigan Agitated Behaviour Scale. Methods This study was conducted in Spain using a multicentre cross-sectional convenience sample of 140 patients who had been admitted to psychiatric hospital units and had presented an episode of psychomotor agitation between 2018 and 2021. Results The Corrigan Agitated Behaviour Scale was used to assess psychomotor agitation. Associated nursing diagnoses, violence directed at professionals and the environment are shown to be predictive values for the severity of the agitation episode. Moderate-severe psychomotor agitation episodes are shown as predictors of violence directed mainly at professionals and the environment. Conclusions There is an urgent need for mental health nurses to have knowledge of the extended clinic in order to care for users and improve their health conditions in dealing with people, with their social, subjective and biological dimension.